First genetic classification of Cryptosporidium and Giardia from HIV/AIDS patients in Malaysia - Lim, Y.A.L.; Iqbal, A.; Surin, Johari; Sim, B.L.H.; Jex, A.R.; Nolan, M.J.; Smith, H.V.; Gasser, R.B. (Elsevier, 2011)
Given the HIV epidemic in Malaysia, genetic information on opportunistic pathogens, such as Cryptosporidium and Giardia, in HIV/AIDS patients is pivotal to enhance our understanding of epidemiology, patient care, management and disease surveillance. In the present study, 122 faecal samples from HIV/AIDS patients were examined for the presence of Cryptosporidium oocysts and Giardia cysts using a conventional coproscopic approach. Such oocysts and cysts were detected in 22.1 and 5.7 of the 122 faecal samples, respectively. Genomic DNAs from selected samples were tested in a nested-PCR, targeting regions of the small subunit (SSU) of nuclear ribosomal RNA and the 60 kDa glycoprotein (gp60) genes (for Cryptosporidium), and the triose-phosphate isomerase (tpi) gene (for Giardia), followed by direct sequencing. The sequencing of amplicons derived from SSU revealed that Cryptosporidium parvum was the most frequently detected species (64 of 25 samples tested), followed by C. hominis (24), C. meleagridis (8) and C. felis (4). Sequencing of a region of gp60 identified C. parvum subgenotype IIdA15G2R1 and C. hominis subgenotypes IaA14R1, IbA10G2R2, IdA15R2, IeA11G2T3R1 and IfA11G1R2. Sequencing of amplicons derived from tpi revealed G. duodenalis assemblage A, which is of zoonotic importance. This is the first report of C hominis, C. meleagridis and C. felis from Malaysian HIV/AIDS patients. Future work should focus on an extensive analysis of Cryptosporidium and Giardia in such patients as well as in domestic and wild animals, in order to improve the understanding of transmission patterns and dynamics in Malaysia. It would also be particularly interesting to establish the relationship among clinical manifestation, CD4 cell counts and genotypes/subgenotypes of Cryptosporidium and Giardia in HIV/AIDS patients. Such insights would assist in a better management of clinical disease in immuno-deficient patients as well as improved preventive and control strategies. (C) 2011 Elsevier B.V. All rights reserved.